A Study on Quantitative Estimation of Secondary Metabolites And In Vitro Dipeptidyl Peptidase IV (DPP-IV) Inhibitory Activity of Hyptissuveolens seed Extract - N. Jagannath; D. Sheela; Rohit Dixit (The Bioscan, 2024)
The increasing prevalence of diabetes has driven research towards natural alternatives for managing the disease. DPP-IV (Dipeptidyl Peptidase-IV) inhibitors play a vital part in regulating blood glucose levels by prolonging the activity of incretin hormones. Natural plant extracts rich in bioactive compounds have shown promising potential as DPP-IV inhibitors. This study focuses on the quantitative analysis of phytochemicals and the evaluation of the inhibitory activity of DPP-IV of a hydroalcoholic extract. Objective: The primary objective of this research has been to quantitatively estimate the Alkaloids, phenols, and flavonoids that make up the phytochemical content of a hydroalcoholic extract and to investigate its DPP-IV inhibitory possibilities using in vitro tests, using sitagliptin as a positive control. Materials and Methods:The DPP-IV inhibitory activity of the extract was determined by spectrophotometric determination. To assess how effectively the extract compares to sitagliptin, percent inhibition and IC50 values were calculated. Total flavonoid, phenolic, and alkaloid contents were quantitatively measured to investigate any correlation between these compounds and the noted inhibitory activity. Results:The hydroalcoholic extract showed to be quite potent on DPP-IV with much higher concentration than sitagliptin needed for attaining the same potency. The IC50 value for an extract was 115.38μg/mL, whereas for sitagliptin it was 44.68μg/mL. Further quantitative evaluation resulted in the finding of the following: flavonoids were found in 2.88 mg/100 mg, phenols in 1.90 mg/100 mg, and alkaloids in 1.92 mg/100 mg, thus flavonoids are in majority. Conclusion: The results indicate that the hydroalcoholic extract possesses notable DPP-IV inhibitory activity, likely driven by its flavonoid content. These results underline the extract's potential as a natural antidiabetic drug and call for more research into its possible medicinal uses.